PEMBUATAN PETA SITUASI SKALA 1 : 500 DUSUN PANDANREJO DAN TEGALMIRI DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , DWI RATRI S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project is the result of a measurement that includes mapping and determining position to produce geographical and spatial elements from the earth's surface. Geographical elements include the natural state on the earth's surface. Spatial elements include the contours and planimetric detail obtained from the measurements that have been presented on the map . In this measurement, the author using the methods of determining the map control framework, the measurement of horizontal control framework, the measurement of the vertical control framework, the measurement of planimetric detail and the high point, the depiction of the digital maps and map correctness testing . The final result obtained is the situation map of location 11 Pandanrejo and Tegalmiri villages, Banyuripan village, Bayat sub-district, Klaten district, Central Java province was drawn by scale of 1:500 in tranverse Universal Mercator projection system (UTM) projection and datum World Geodetic System (WGS 84).